Angle-based Formation Shape Control with Velocity Alignment. Issue 2 (2020) - Chen, Liangming; Cao, Ming; Sun, Zhiyong; Anderson, Brian D.O.; Li, Chuanjiang
Abstract: With the rapid development of sensor technology, bearing/angle measurements are becoming cheaper and more reliable, which motivates the study of angle-based formation shape control. This work studies how to achieve angle-based formation control and velocity alignment at the same time, in which all agents can form a desired angle-rigid formation and translate with the same velocity simultaneously. The agents' communication topology for the achievement of velocity alignment is described by a connected graph, while the formation shape is determined by a set of angles that are associated with triangles within the formation and computed using bearing measurements. A simulation example validates the effectiveness of the theoretical results.